Positive and Negative Factors of Economic Development in Economic History of South Korea - Park Jong Min; Ko Young Cheol (Модернизация, инновация, развитие, 2017)
Purpose: the aim of the article is to analyze the Korean economic strategy from the beginning of its development until modern stage. Examination of how this strategy has changed depending on changes within domestic and international economic environment, assumptions, set goals, their effectiveness and significance of all the taken measures. It will demonstrate waypoints for the future economic development and will become a trigger towards recognition of the successful development of the Korean economy by other countries. Methods: the methodological bases of this article are the economic and statistical methods of analysis of the Korean economys, graphical methods displaying economic indicators. Results: economic history of South Korea over the past century shows the positive and negative factors of the development from an economically weak country into a developing country. The history of the Japanese occupation of Korea, lasting from 1910 to 1945, showed that for a country which has lost its national sovereignty, expropriated the state's economy has no effect after the restoration of independence, and that the economy cannot develop in conditions of chaos within the political, economic and social spheres. Even after the establishment of a military dictatorship, it is possible to note that despite limitations of citizens’ rights, the economy can still grow if the people want it. In addition to the development of internal political system, unstable factors in the process of promotion of social reforms and hastily adopted policy of "open doors" in order to enhance the international status are unreasonable political, economic and social changes. In turn, the inability to control currency exchange in Asian countries, which is a policy of economic development, has shown the existence of a risk of national bankruptcy. Moreover, the adoption of policies of excessive decrease of interest rates in order to revive the recession may be counterproductive in countries with a developed economies and lead to an economic crisis. Conclusions and Relevance: for the last century, the changes that happened in the economic history of the Republic of Korea made it the model case of progressive economic development of developing countries. The history of Korea's economic development suggests presence of both positive and negative factors. Within the positive factors of the economic development of the Republic of Korea it is possible to note: planning of economic development, a potential for development of technology, ability to control currency, financial crisis management and free trade agreements. Negative factors for economic development were the loss of national sovereignty, disturbances in political, economic and social fields. In addition, people's desire to develop the national economy shows that the economic development could be accomplished successfully.